An overview of third, fourth and sixth cranial nerve palsies in the setting of COVID-19: A case report and systematic review. Issue 49 (9th December 2022) - Meshref, Mostafa; Shaheen, Nour; Swed, Sarya; Ibrahim, Mohamed; Mostafa, Mostafa Reda; Algazar, Mohamed Osman; Dobs, Monica; Elsayed, Sarah Ibrahim; Amro, Yara; Afsa, Ahmed; Morra, Mostafa Ebraheem
Abstract : Background: Covid-19 has serious sequelae that may be poorly understood, underreported, and, as a result, not diagnosed promptly, such as variations in clinical manifestations of hyperinflammation among people infected with SARS-CoV-2. ophthalmoplegia can be one of these manifestations. Methods: We are reporting a 55-year-old male patient with unilateral diplopia considering it as a case of multisystem inflammatory syndrome in adults. We also reviewed the literature systematically for the previously reported studies/cases with third, fourth and sixth cranial nerve palsies due to or after Covid-19. Results: The literature search yielded 17 studies reporting 29 patients. 71.4% of the patients were males with a mean age of 42.23 years. Ophthalmological symptoms took 9.7 days to appear after the respiratory involvement. All patients had diplopia as part of their visual symptoms. 41.4% of the patients had unilateral sixth nerve palsy, 24% had bilateral sixth nerve involvement, 17% had fourth nerve involvement, and 27.6% had third nerve involvement. Conclusion: Ophthalmoplegia is considered presenting symptom of Covid-19. Further research is needed to detect all neuro-ophthalmological manifestations of Covid-19.